Campur Kode Bahasa Inggris Dalam Novel Wedding Agreement Karya Mia Chuz Dan Implikasinya Terhadap Pembelajaran Teks Iklan, Slogan, Dan Poster Kelas VIII SMP - Kharisma Devi; Albertus Purwaka; Indra Perdana; Isti Prihatini; Frans Jepi Nexon; Sutrisno Sutrisno (Universitas Palan, 2023)
The Wedding Agreement novel by Mia Chuz is a form of written literature containing code-mixed language elements. Code mixing is presented in the form of inserting English elements into Indonesian. The purpose of this study was to describe the form of linguistic elements, the causal factors and the function of mixing the English code in the novel Wedding Agreement by Mia Chuz and the implications for learning advertising texts, slogans and posters for class VIII SMP. The approach used in this study is a qualitative approach using content analysis techniques. The results of the study found 120 data containing the form of linguistic elements of English code mixing in the form of inserting elements in the form of words, phrases, basters, and clauses as well as 7 causal factors and 8 functions of English code mixing in Mia Chuz's novel Wedding Agreement.